Chlorophylls, ligands and assembly of light-harvesting complexes in chloroplasts - Hoober, J. Kenneth (Springer Netherlands, 2007)
Chlorophyll (Chl) b serves an essential function in accumulation of light-harvesting complexes (LHCs) in plants. In this article, this role of Chl b is explored by considering the properties of Chls and the ligands with which they interact in the complexes. The overall properties of the Chls, not only their spectral features, are altered as consequences of chemical modifications on the periphery of the molecules. Important modifications are introduction of oxygen atoms at specific locations and reduction or desaturation of sidechains. These modifications influence formation of coordination bonds by which the central Mg atom, the Lewis acid, of Chl molecules interacts with amino acid sidechains, as the Lewis base, in proteins. Chl a is a versatile Lewis acid and interacts principally with imidazole groups but also with sidechain amides and water. The 7-formyl group on Chl b withdraws electron density toward the periphery of the molecule and consequently the positive Mg is less shielded by the molecular electron cloud than in Chl a. Chl b thus tends to form electrostatic bonds with Lewis bases with a fixed dipole, such as water and, in particular, peptide backbone carbonyl groups. The coordination bonds are enhanced by H-bonds between the protein and the 7-formyl group. These additional strong interactions with Chl b are necessary to achieve assembly of stable LHCs.